An Interesting Case of Epiphytism of Euphorbia neriifolia Linn. From Gujarat - Billore, K. V. (Indian Forester, 1988)
An interesting record of Euphorbia neriifolia Linn. growing epiphytically on Aegle marmelos (L) Corr., hitherto unreported has beed presented.